Analysis of humoral and cellular immune activation up to 21 months after heterologous and homologous COVID-19 vaccination - Davide Torre; Chiara Orlandi; Chiara Orlandi; Ilaria Conti; Simone Barocci; Eugenio Carlotti; Mauro Magnani; Mauro Magnani; Anna Casabianca; Anna Casabianca; Giuseppe Stefanetti; Giuseppe Stefanetti (Frontiers in Immunology)
To address the COVID-19 pandemic, diverse vaccination strategies, including homologous and heterologous schedules, were employed to enhance immune protection. This study evaluates the long-term humoral and cellular immune responses in individuals vaccinated with homologous (ChAdOx1-S/ChAdOx1-S [ChAd/ChAd]) and heterologous (ChAdOx1-S/BNT162b2 [ChAd/BNT]) schedules, followed by a third-dose mRNA booster (BNT162b2 [BNT] or mRNA-1273). Anti-Spike IgG titers were measured at 9-, 12-, and 21-months post-primary vaccination (corresponding to 3-, 6-, and 15-months post-booster), while SARS-CoV-2-specific B- and T-cell responses were assessed at 21-months post-booster. Antibody titers declined by 12-months post-primary vaccination, regardless of the third dose administered, and increased significantly by 21-months, potentially due to a fourth dose (BNT or mRNA-1273) or natural SARS-CoV-2 infection. The heterologous ChAd/BNT schedule elicited a stronger and more durable immune response than the homologous ChAd/ChAd, as evidenced by higher anti-Spike IgG titers, increased IgM-/IgG+ memory B-cell activation, and enhanced cytotoxic CD8+ T-cell cytokine expression in infected individuals. SARS-CoV-2 infection further boosted humoral and cellular responses, with infected individuals showing higher anti-Spike IgG titers and greater CD8+ T-cell activation compared to uninfected individuals. These findings highlight the benefits of heterologous vaccination schedules and the role of infection-driven immune activation, providing valuable insights for optimizing vaccination strategies to improve long-term immunity against SARS-CoV-2.